Reviving an Annual Event: Increasing Community Engagement and Responding to COVID-19 - Chrissy O'Grady (Journal of New Librarianship, 2022)
Librarians often use creativity to modify existing events or create new ones in response to patron needs. Six months into my first librarian position, I took over a long-standing Poem in Your Pocket library event from a colleague. I began planning the event in January 2020, before the pandemic, and had to pivot several times over the past three years of organizing the event in response to community needs, personal needs, and pandemic related restrictions. I will discuss how I revived the existing Poem in Your Pocket event into a community-authored celebration, and how the feedback I have received from faculty, students, and community members has solidified my drive to continue organizing this event, despite taking on more responsibilities within my job.